Bilateral Subclavian Steal Syndrome - Reza Amini; Heather L. Gornik; Leslie Gilbert; Sue Whitelaw; Mehdi Shishehbor (Case Reports in Cardiology)
Bilateral subclavian steal syndrome is a rare condition. It is usually due to reversal of vertebral blood flow in the setting of bilateral proximal subclavian or left subclavian plus innominate artery severe stenosis or occlusion. This finding may cause cerebral ischemia related to upper extremities exercise. We report a case of bilateral subclavian steal secondary to total occlusion of the innominate and left subclavian arteries in a patient who presented with cardiomyopathy and flow reversal in the right carotid and bilateral vertebral arteries.